HUBUNGAN KEMAMPUAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI BIRO TATA PEMERINTAHAN SEKRETARIAT DAERAH PROVINSI JAWA TENGAH - Gama Maula Rahman; Hardi Warsono; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The human resources of the organization has a variety of characteristics, including the ability to work, motivation and performance it has. These three components are closely related and are in themselves employees who carry out everyday tasks. The success of an organization is influenced by the performance of employees. This research was conducted to determine the relationship of ability and motivation with employee performance Bureau Regional Secretariat Governance of Central Java Province. In this study, using quantitative research techniques nonprobality census sampling sampling in which 47 respondents. Testing hypotheses using Kendall Rank as an ordinal of data. The studies results shows that (Z count (2.46)> Z table (1.96)) there is an acceptance of the hypothesis that there is a positive and significant correlation between the ability of employees (X1) and Performance (Y). (Z count (2.94)> Z table (1.96)) there is an acceptance of the hypothesis that there is a positive and significant relationship between motivation (X2) and Performance (Y). (ƒÓ2 count (104.742)> ƒÓ2table (71.308)). The acceptance of the hypothesis that there is a positive and significant correlation between the ability of employees (X1) and motivation (X2) and Performance (Y).